Efisiensi Mikroenkapsulasi Ekstrak Kulit Buah Naga Super Merah (Hylocereus costaricensis) Tersalut Maltodekstrin Berdasarkan Kecepatan Pengadukan: Microencapsulation Efficiency of Super Red Dragon Fruit (Hylocereus costaricensis) Peel Extract Coated with Maltodextrin Based on Stirring Speed - Jaya Hardi; Dian Citra; Syamsuddin; Dwi Juli Pusptasari (KOVALEN: Jurnal Riset Kimia, 2020)
Extract of super red dragon fruit peel has an antioxidant activity that can prevent free radicals from outside and its activity can be maintained by the coating of super red dragon fruit peel extract with maltodextrin The coating efficiency of super red dragon fruit peel extract with maltodextrin can be controlled with the speed of stirring during microencapsulation experiment. In order to obtain the highest microencapsulation efficiency and compare the antioxidant activity of super red dragon fruit peel extract before and after microencapsulation experiment. The study of coating efficiency has been done with microencapsulation that was carried out using the freeze-drying technique. During the microencapsulation of super red dragon fruit peel extract with freeze-drying technique, stirring speed in the microencapsulation process was 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, and 1400 rpm respectively. From the microencapsulation process of super red dragon fruit peel extract coated with maltodextrin, it was obtained the highest microencapsulation efficiency at stirring speed of 800 rpm, which was 66.85% and had a particle size of 14.24 µm. It can be concluded that the antioxidant activity before and after encapsulation included a very weak category with IC50 values of 205.42 ppm for extracts and 246.32 ppm for microcapsules. Keywords: Super red dragon fruit peel, freeze-drying, microencapsulation, maltodextrin